Pendampingan dan Pemberdayaan Masyarakat Desa Prancak dalam Pemanfaatan Potensi Lokal Melalui Pengolahan Gadung - Hajar (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
The selection of this assisted subject is not This selection of assisted subjects is not motivated by the easy location of the place of service, but on objective basic reasons related to the importance of this assistance for with the importance of this assistance for society in general. The title of the service we chose is assistance in the production and marketing of Gadung chips and chili chips to rebuild the Assalam group. and Chili chips to rebuild the Assalamah group and raise the selling price value of Gadung which is classified as a rare (Endemic) plant. Gadung is classified as a rare plant (Endemic). Empowerment is a process that aims to make society or individuals better through various through a variety of ways, both through participation, control or intervention process in every line of the community's life. of community life. The focus of the service is more on how the people of Prancak village can utilize Gadung tubers as an effort to increase the income and welfare of the community and to release the and community welfare and to release dependence on agricultural products whose conditions are increasingly uncertain. This service has helped improve farmers' creativity, economy, and utilization of agricultural products.